Resolusi Konflik pada Keluarga Long Distance Marriage (Studi Fenomenologi) - Rosyadi. B. R Rosyadi. B. R; Sholahudin Amrullah; Suryadi Suryadi (Bulletin of Counseling and Psychotherapy, 2022)
The purpose of this study was to find out a family who underwent a long distance marriage. In a marriage husband and wife try to manage their household such as adjusting and working with their respective partners. Along with the increasing need for family life, high competition in pursuing a career, and the education they undergo, husband and wife often have to live separately. This study uses a qualitative approach to phenomenology. Data collection using interviews, observations, and documentation. Data analysis in this study using Miles and Huberman & Saldana including a summary of data condensation data, data presentation and conclusion drawing. The study was conducted on 5 married couples who were undergoing long-distance marriages in Bloro village in Kec. visit. Selected respondents were married for ± 1 to ± 10 years, married for ± 1 month to ± 3 years, and the meeting between husband and wife occurred once a year. The results of the study show that there are several factors that make a married couple undergo a long distance marriage, including work, education, and the necessities of life, namely the desire to have their own home. while the effort to maintain marriage is to positive thinking, openness, certainty, in social networks and distributing tasks.